Hospital chaplains as ethical consultants in making difficult medical decisions - Głusiec, Waldemar (Journal of medical ethics, 2022)
Background and aims Few Polish hospitals have Hospital Ethics Committee (HECs) and the services are not always adequate. In this situation, the role of HECs, in providing, among others, ethical advice on the discontinuation of persistent therapies, may be taken over by other entities. The aim of our research was to investigate, how often and on what issues hospital chaplains are asked for ethical advice in reaching difficult medical decisions. Methods A survey of 100 Roman Catholic chaplains was conducted, that is, at least 10% of all chaplains currently working in Polish hospitals. Results Of the participants, 29% confirmed receiving requests for advice in making a morally difficult medical decision. Receiving this type of request was not conditional on the place of their service, duration of their pastoral mission or HEC membership. The largest group of chaplains (21%) encounter questions concerning the ethical dilemmas associated with discontinuing persistent therapy. Patients and their families most often raise issues related to the methods of birth control, and the medical staff raise the issue of termination of pregnancy—as reported by 9% and 15% of chaplains, respectively. Most of the chaplains asked for help (79%) experience a deficit of specialist knowledge in the area of medicine or ethics. Conclusions In order to improve the quality of ethical consultations in Polish hospitals, in addition to further development of HECs, it is postulated to develop a system for bioethical education of chaplains.